2017
DOI: 10.4274/meandros.39974
|View full text |Cite
|
Sign up to set email alerts
|

A Retrospective Study of the Prevalence of Cemental Tear in a Sample of the Adult Population Applied Ondokuz Mayis University Faculty of Dentistry

Abstract: Anah tarKe li me ler Radyografi, prevalans, semental ayrılma

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 13 publications
0
6
1
Order By: Relevance
“…However, this was in disagreement with earlier studies that reported the association of anterior teeth with increased cemental tears (Leknes et al, 1996;Lin et al, 2011). Moreover, maxillary central incisors have been shown to be more frequently affected amongst the anterior teeth (Keskin & Güler, 2017;Qari et al, 2019), even though others did not report any significant difference between the maxillary and mandibular central incisors (Lin et al, 2011). A summary of the case reports reviewed on 41 patients and 58 teeth revealed that cemental tears occurred in 34 (59%) anterior teeth, 17 (29%) premolars and 7 (12%) molars (Table 1).…”
Section: Tooth Typecontrasting
confidence: 64%
See 4 more Smart Citations
“…However, this was in disagreement with earlier studies that reported the association of anterior teeth with increased cemental tears (Leknes et al, 1996;Lin et al, 2011). Moreover, maxillary central incisors have been shown to be more frequently affected amongst the anterior teeth (Keskin & Güler, 2017;Qari et al, 2019), even though others did not report any significant difference between the maxillary and mandibular central incisors (Lin et al, 2011). A summary of the case reports reviewed on 41 patients and 58 teeth revealed that cemental tears occurred in 34 (59%) anterior teeth, 17 (29%) premolars and 7 (12%) molars (Table 1).…”
Section: Tooth Typecontrasting
confidence: 64%
“…Tooth type was not reported to be a significant risk factor in two recent observational studies (Keskin & Güler, 2017;Özkan & Özkan, 2020). However, this was in disagreement with earlier studies that reported the association of anterior teeth with increased cemental tears (Leknes et al, 1996;Lin et al, 2011).…”
Section: Tooth Typementioning
confidence: 73%
See 3 more Smart Citations